ORIENTALISME DAN ISLAM DALAM PERGULATAN SEJARAH - Haqan, Arina (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
Western interest in Islam can be seen as the start of the movement to study Islam since the 12th century. At that time, some western monks ever came to Andalusia in the heyday of the East. They learn in schools there, translating the Koran and Arabic language books into their language in various fields of science. Among them is Jerbert who was elected Pope of Rome in 999 AD, Pierrele Aenere (1156-1092), and Gerard de Gremone (1187-1114). After returning to their home areas they begin to teach the science that has been obtained. This article discusses about Orientals, ranging from the definition, history until its development. Including the development of studies of Orientals is the quality Orientalis, subjectivist or objectivist. According to the authors, the quality classification is necessary as a critique of Orientals lunge. At the end of the study say that there are two models of Orientals Islamic studies. A view of them remains as subjective first period with a condescending attitude towards the East. But others, has seen Islam objectively in terms of pure science